2015
DOI: 10.1007/s00404-015-3740-z
|View full text |Cite
|
Sign up to set email alerts
|

Emergency peripartum hysterectomy: 2-year experiences in non-tertiary center

Abstract: The results of this study showed the most important risk factors associated with peripartum hysterectomy to be uterine atony, grand multiparity, and uterine rupture. Maternal intensive care, maternal death, neonatal death, or neonatal intensive care were associated with home delivery or delayed presentation at hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
0
6
1
Order By: Relevance
“…1); 128 had been included in the previous meta-analysis . 1 This update includes 26 additional studies and presents data for an additional 7,741 women in 22 nations 8–33 (Appendix 3, available online at http://links.lww.com/AOG/C968). Eight of the new studies were from countries from which we previously did not have data: Belgium, France, Germany, Romania, Slovakia, Sweden, Iceland, and Papua New Guinea.…”
Section: Resultsmentioning
confidence: 99%
“…1); 128 had been included in the previous meta-analysis . 1 This update includes 26 additional studies and presents data for an additional 7,741 women in 22 nations 8–33 (Appendix 3, available online at http://links.lww.com/AOG/C968). Eight of the new studies were from countries from which we previously did not have data: Belgium, France, Germany, Romania, Slovakia, Sweden, Iceland, and Papua New Guinea.…”
Section: Resultsmentioning
confidence: 99%
“…The higher complication rate is expected in the emergent cases than scheduled surgery. The bladder injury that is the most common complication was observed as 3-20% in several studies 3,7,12,17,23 . A higher incidence of bladder injury(27.2%) was stated in our study in reference to the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Kazi found that emergent peripartum hysterectomy was performed for hemorrhage primarily due to uterine atony 12 . Senturk et al put forward that the incidence of PPH was higher in the east of Turkey and the main indication was uterine atony and rupture 17 . The increasing use of uterotonics and cesarean rate may explain the conversion of main indication from uterine atony to abnormal invasive placentation for PPH 3,6,19,[22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“… 13 There are several studies that have assessed PPHs, and the incidence may change among countries and centers depending on whether they have sufficient antenatal care for pregnancies. In some studies 7 14 15 16 17 from Turkey, the incidence of PPH was established between 0.3 and 5.38 for every thousand deliveries. Sharma et al 3 found a much higher incidence, of 6.9 for every thousand deliveries.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Kazi 12 found that emergency PPH was performed in cases of hemorrhage primarily due to uterine atony. Senturk et al 17 suggested that the incidence of PPH was higher in Eastern Turkey, and the main indication was uterine atony and rupture. The increasing use of uterotonics and rate of cesarean sections may explain the shift on the main indication for PPH from uterine atony to abnormal invasive placentation.…”
Section: Discussionmentioning
confidence: 99%